Biosolubilization of phosphate by strains of Trichoderma in vitro and in greenhouse in three varieties of Coffea arabica - Arias, Rosa; Torres, Alberto; Perea, Yamel; Cruz, Yadeneyro (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Coffee soils have a low availability of phosphorus, the use of phosphate-solubilizing Trichoderma strains is a promising sustainable strategy for the management of phosphorus deficiencies. In this study in Mexico, we evaluated 10 strains of Trichoderma from the andosol soil of coffee plantations in Mexico and their capacity for phosphate solubilization in vitro, and their impact on the growth of coffee seedlings of three varieties (Anacafé, Costa Rica and Marsellesa) were evaluated. The tested microorganisms showed high phosphorus solubilization, the phosphorus solubilization ranged between 2.41 and 7.40 mg.mL-1. The maximum phosphate solubilizing activity was observed using two strains of Trichoderma harzianum 75.73 (Th53) and 74.62 mg.mL-1 (Th48) for calcium phosphate (Ca2PO4) and three strains of T. asperellum 22.99 (Th57), 22.90 (Th49) and 21.55 mg.mL-1 (Th40) for aluminum phosphate (AlPO4). In both calcium (Ca2PO4) and aluminum phosphate (AlPO4), a decrease in the pH of the medium was detected, from 4.81 to 3.73 and from 3.38 to 2.75, respectively. In the Anacafé variety, the application of two strains of T. harzianum (Th48 and Th53) favored greater availability of phosphorus in the substrate, while in the Costa Rica and Marsellesa varieties the available phosphorus of the substrate was greater with T. harzianum (Th48). Inoculation with these Trichoderma strains is potentially important for the solubilization of insoluble phosphorus and the development of coffee plants.